THE EFFECT OF ORGANIZATIONAL CLIMATE AND WORK ETHIC ON EMPLOYEE PERFORMANCE WITH EMPLOYEE PLANNING AS AN INTERVENING VARIABLE AT PT PLN (PERSERO) UP3 PADANGSIDIMPUAN - Yessi Indra; Sri Rahayu; Kiki Farida Ferine (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the influence of Organizational Climate and Work Ethic on Employee Performance with Employee Planning as an intervening variable. The study was conducted in an agency with 86 respondents. The research method used is a quantitative approach with Partial Least Square–Structural Equation Modeling (PLS-SEM) analysis techniques. The results of the study indicate that Work Ethic has a positive and significant effect on Employee Performance and a significant effect on Employee Planning. Organizational Climate does not directly affect Employee Performance, but has a significant effect on Employee Planning. In addition, Employee Planning has a significant effect on Employee Performance. In terms of mediation, Employee Planning is able to significantly mediate the effect of Work Ethic on Employee Performance, but cannot mediate the effect of Organizational Climate on Employee Performance. These findings indicate the importance of improving employee planning in improving performance through work ethic.